Synthesis, Characterization, and Biological Evaluation of Gabapentinoid Hybrids with Isoindole-1,3(2H)-Dione Moiety as Potential Antioxidant, Antimicrobial, and Anticancer Agents - Mirna Jabbour; Mohammad Ammar Al-Khayat; Mahmoud Al-Ktaifani (Journal of Chemistry)
Purpose. To synthesize new isoindole-1,3(2H)-dione derivatives by molecular hybridization of gabapentin and pregabalin with phthalic anhydride derivatives and to evaluate their biological activity as promising antioxidant, antimicrobial, and anticancer agents. Method. Molecular hybridization was successfully achieved by two procedures; synthesized compounds were characterized using analytical and spectral methods. The free radical scavenging properties of synthesized compounds were evaluated using the DPPH method. The antibacterial activity of synthesized compounds and parent compounds was evaluated against two microbial Gram-positive and Gram-negative strains by the well diffusion method. Furthermore, we have studied the effect of compounds on proliferation, cell cycle, and cell death in two human cancer cell lines (Caco-2 and HCT-116). Results. Compounds 1, 3, and 4 exhibited a good free radical scavenging effect, and compound 3 is the most effective with IC50 value of 2.525 μmol/mL. All compounds showed antibacterial activity against Escherichia coli and Staphylococcus aureus related to concentration, while parent drugs did not exhibit any antibacterial effect. Compounds 1 and 2 showed a good zone of inhibition against E. coli at micromolar concentrations, and they are more effective than Gentamicin Sulfate. Treatment with the studied compounds suppresses proliferation, arrests progress throughout the cell cycle, and induces apoptosis in Caco-2 and HCT-116 cancer cells. Compound 2 is highly effective against Caco-2 cells and more effective than thalidomide, with IC50 value less than 1 μmol/L. Conclusion. Our results showed that molecular hybridization of gabapentin and pregabalin in the isoindole-1,3(2H)-dione moiety results in promising anticancer and antimicrobial molecules. Results of this preliminary study show that halogenation of the isoindole-1,3(2H)-dione moiety improves antimicrobial and anticancer activity and that tetra-brominated derivatives are comparable to or more effective than related tetra-chlorinated derivatives.